2016
DOI: 10.1074/jbc.m115.689026
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of the Poly-γ-glutamate Tail of F420 Requires Both Domains of the F420:γ-Glutamyl Ligase (FbiB) of Mycobacterium tuberculosis

Abstract: Cofactor F 420 is an electron carrier with a major role in the oxidoreductive reactions of Mycobacterium tuberculosis, the causative agent of tuberculosis. A ␥-glutamyl ligase catalyzes the final steps of the F 420 biosynthesis pathway by successive additions of L-glutamate residues to F 420 -0, producing a poly-␥-glutamate tail. The enzyme responsible for this reaction in archaea (CofE) comprises a single domain and produces F 420 -2 as the major species. The homologous M. tuberculosis enzyme, FbiB, is a two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 48 publications
0
57
0
Order By: Relevance
“…Subsequently, LPPG (L-lactyl-2-diphospho-5 0 -guanosine) is proposed to be synthesized from 2-phospho-L-lactate by CofC (Grochowski et al, 2008) and transferred to F o by CofD (also known as FbiA) (Choi et al, 2001;Graupner and White, 2001;Graupner et al, 2002). The resulting LPPG sidechain is finally elongated with glutamate residues by the F 420 :γ-L-glutamyl ligase CofE (also known as FbiB) (Choi et al, 2001;Li et al, 2003;Nocek et al, 2007) that is fused with an FMNdependent oxidoreductase in Actinobacteria (Bashiri et al, 2016). For reasons still not understood, the number of glutamate residues added varies between organisms, ranging from two to three in most methanogens (Gorris and van der Drift, 1994), four to five in Methanosarcina (Gorris and van der Drift, 1994) and five to seven in Mycobacterium .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, LPPG (L-lactyl-2-diphospho-5 0 -guanosine) is proposed to be synthesized from 2-phospho-L-lactate by CofC (Grochowski et al, 2008) and transferred to F o by CofD (also known as FbiA) (Choi et al, 2001;Graupner and White, 2001;Graupner et al, 2002). The resulting LPPG sidechain is finally elongated with glutamate residues by the F 420 :γ-L-glutamyl ligase CofE (also known as FbiB) (Choi et al, 2001;Li et al, 2003;Nocek et al, 2007) that is fused with an FMNdependent oxidoreductase in Actinobacteria (Bashiri et al, 2016). For reasons still not understood, the number of glutamate residues added varies between organisms, ranging from two to three in most methanogens (Gorris and van der Drift, 1994), four to five in Methanosarcina (Gorris and van der Drift, 1994) and five to seven in Mycobacterium .…”
Section: Introductionmentioning
confidence: 99%
“…However, no masses corresponding to F420-0 were identified in any of the LC-MS traces from the FbiD:FbiA coupled assays, suggesting that an enzyme other than FbiD or FbiA catalyzes dehydro-F420-0 reduction. We have previously shown that full-length FbiB consists of two domains: an N-terminal domain that is homologous to the archaeal -glutamyl ligase CofE 21,33 , and a C-terminal domain of the NTR fold 34 that binds to FMN and has no known function 20 , but is essential for extending the poly--glutamate tail.…”
Section: Fbid/cofc Use Phosphoenolpyruvate Rather Than 2-phospho-l-lmentioning
confidence: 99%
“…The two branches then merge at the reaction catalyzed by the transferase FbiA/CofD, where the 2-phospho-L-lactyl moiety of LPPG is transferred to Fo, forming F420-0 18,19 . Finally, the -glutamyl ligase (FbiB/CofE) catalyzes the poly-glutamylation of F420 to generate mature F420, with poly--glutamate tail lengths of ~2-8, depending on species 20,21 .…”
mentioning
confidence: 99%
See 2 more Smart Citations